Answer:
The answer is
![y = (rw - 6f)/(f)](https://img.qammunity.org/2021/formulas/mathematics/college/yfho73quo93ozd7q100c0gybp5v5do6njp.png)
Explanation:
![(rw)/(6 + y) = f](https://img.qammunity.org/2021/formulas/mathematics/college/xzrn47z9nz1xestsuc7by6y54hz680bxgk.png)
Cross multiply
We have
f(6 + y) = rw
6f + fy = rw
Move 6f to the right side of the equation to make fy stand alone
That's
fy = rw - 6f
Divide both sides by f to isolate y
That's
![(fy)/(f) = (rw - 6f)/(f)](https://img.qammunity.org/2021/formulas/mathematics/college/af8clykfefu9c8hmmlarsj3yrw9r9js7s7.png)
We have the final answer as
![y = (rw - 6f)/(f)](https://img.qammunity.org/2021/formulas/mathematics/college/yfho73quo93ozd7q100c0gybp5v5do6njp.png)
Hope this helps you